Treatment Outcomes of Percutaneous Radiofrequency Ablation for Hepatocellular Carcinomas: Effects of the Electrode Type and Placement Method - Park, Jiyeon; Lee, Min Woo; Ahn, Soo Hyun; Han, Seungchul; Min, Ji Hye; Cha, Dong Ik; Song, Kyoung Doo; Kang, Tae Wook; Rhim, Hyunchul (Korean Journal of Radiology, 2023)
Objective: To investigate the association among the electrode placement method, electrode type, and local tumor progression (LTP) following percutaneous radiofrequency ablation (RFA) for small hepatocellular carcinomas (HCCs) and to assess the risk factors for LTP. Materials and Methods: In this retrospective study, we enrolled 211 patients, including 150 males and 61 females, who had undergone ultrasound-guided RFA for a single HCC < 3 cm. Patients were divided into four combination groups of the electrode type and placement method: 1) tumor-puncturing with an internally cooled tip (ICT), 2) tumor-puncturing with an internally cooled wet tip (ICWT), 3) no-touch with ICT, and 4) no-touch with ICWT. Univariable and multivariable Cox proportional-hazards regression analyses were performed to evaluate the risk factors for LTP. The major RFA-related complications were assessed. Results: Overall, 83, 34, 80, and 14 patients were included in the ICT, ICWT, no-touch with ICT, and no-touch with ICWT groups, respectively. The cumulative LTP rates differed significantly among the four groups. Compared to tumor puncturing with ICT, tumor puncturing with ICWT was associated with a lower LTP risk (adjusted hazard ratio [aHR] = 0.11, 95% confidence interval [CI] = 0–0.88, P = 0.034). However, the cumulative LTP rate did not differ significantly between tumorpuncturing with ICT and no-touch RFA with ICT (aHR = 0.34, 95% CI = 0.03–1.62, P = 0.188) or ICWT (aHR = 0.28, 95% CI = 0–2.28, P = 0.294). An insufficient ablative margin was a risk factor for LTP (aHR = 6.13, 95% CI = 1.41–22.49, P = 0.019). The major complication rates were 1.2%, 0%, 2.5%, and 21.4% in the ICT, ICWT, no-touch with ICT, and no-touch with ICWT groups, respectively. Conclusion: ICWT was associated with a lower LTP rate compared to ICT when performing tumor-puncturing RFA. An insufficient ablation margin was a risk factor for LTP.
Keywords: Carcinoma, Hepatocellular; Catheter Ablation; Electrodes; Female; Humans; Liver Neoplasms; Male; Radiofrequency Ablation; Retrospective Studies; Treatment Outcome; Hepatocellular carcinoma; Internally cooled tip; Internally cooled wet tip; Local tumor progression; Radiofrequency ablation